Block of Counter-Regulation By Inhibition of Protein Synthesis Sensitizes Cancer Cells to IRE1a-Mediated Apoptosis Following Unfolded Protein Response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Effect of Idelalisib on PKC beta/NF-kappa B regulation in stromal cells of chronic lymphocytic leukemia - Lutzny-Geier, Gloria; Handl, Sarah Annika; Von Heydebrand, F.; Wilke, J.; Kremer, Anna-Lena; Mackensen, Andreas; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Exploring CAR T-Cell Dynamics: Balancing Potent Cytotoxicity and Controlled Inflammation in CAR T-Cells Derived from Systemic Sclerosis and Myositis Patients - Dingfelder, Janin; Taubmann, Jule; von Heydebrand, Franziska; Aigner, Michael; Bergmann, Christina; Knitza, Johannes; Park, Soo; Cheng, Joseph K.; Van Blarcom, Thomas; Schett, Georg; Mackensen, Andreas; Lutzny-Geier, Gloria (International Journal of Molecular Sciences, 2025)
Systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and idiopathic inflammatory myositis (IIM) are autoimmune diseases managed with long-term immunosuppressive therapies. Hu19-CD828Z, a fully human anti-CD19 chimeric antigen receptor (CAR) with a CD28 costimulatory domain, is engineered to potently deplete B-cells. In this study, we manufactured Hu19-CD828Z CAR T-cells from peripheral blood of SLE, IIM, and SSc patients and healthy donors (HDs). CAR-mediated, CD19-specific activity of these cells was evaluated in vitro by assessing cytotoxicity, cytokine release, and proliferation assays in response to autologous CD19+ B-cells, the CD19+ NALM-6 B-cell line, or a CD19− U937 non-B-cell line as targets. The results demonstrated an increased proliferation of Hu19-CD828Z CAR T-cells and dose-dependent cytotoxicity against primary autologous and NALM-6 B-cells compared to non-transduced controls or co-cultures with non-B-cells. Notably, autoimmune-patient-derived CAR T-cells produced lower levels of inflammatory cytokines than healthy-donor-derived CAR T-cells in response to CD19+ B-cell targets. These data support the potential of Hu19-CD828Z and its therapeutic cell product KYV-101 as a therapeutic strategy to achieve deep B-cell depletion in SLE, IIM, and SSc patients, and highlights its promise for broader application in B-cell-driven autoimmune disorders.
CRIS-Team Scopus Importer:2025-01-31
Keywords: autoimmune diseases; chimeric antigen receptor; cytokines; idiopathic inflammatory myositis; systemic lupus erythematosus; systemic sclerosis; T-cells

Fully Human Anti-CD19 CAR T Cells Derived from Systemic Lupus Erythematosus Patients Exhibit Cytotoxicity with Reduced Inflammatory Cytokine Production - Dingfelder, Janin; Aigner, Michael; Taubmann, Jule; Minopoulou, Ioanna; Park, Soo; Kaplan, Charles D.; Cheng, Joseph K.; Van Blarcom, Tom; Schett, Georg; Mackensen, Andreas; Lutzny-Geier, Gloria (Transplantation and Cellular Therapy, 2024)
KYV-101 is an autologous anti-CD19 chimeric antigen receptor (CAR)-T cell therapy under investigation for patients with B-cell driven autoimmune diseases. Hu19-CD828Z is a fully human anti-CD19 CAR designed and demonstrated to have a favorable clinical safety profile. Since anti-CD19 CAR T cells target and kill B cells in both circulation and tissues, the treatment with Hu19-CD828Z CAR T cells offers great potential in depleting autoreactive B cells. Demonstrate that Hu19-CD828Z CAR T cells manufactured from cryopreserved leukaphereses from patients with systemic lupus erythematosus (SLE) exhibit CAR-mediated and CD19-dependent cytokine release, proliferation and cytotoxicity when co-cultured with autologous primary B cells. T cells were enriched from cryopreserved leukaphereses from SLE patients or healthy donors (HD). CAR T cells were generated by transducing these cells with a lentiviral vector encoding Hu19-CD828Z. CAR-mediated and CD19-dependent activity was monitored in vitro in a set of cytotoxicity, cytokine release, and proliferation studies, in response to autologous primary CD19+ B cells, a CD19+ cell line (NALM-6), or a CD19− cell line (U937). Hu19-CD828Z CAR T cells produced from SLE patients or HD induced greater proliferation and dose-dependent cytotoxicity against both autologous primary B cells and the CD19+ NALM-6 cells than nontransduced control T cells or co-cultures with a CD19− cell line. Interestingly, there was lower inflammatory cytokine production from SLE patient-derived CAR T cells compared to HD donor-derived CAR T cells with either CD19+ cells or primary B cells. Hu19-CD828Z CAR T cells generated from SLE patient lymphocytes demonstrate CAR-mediated and CD19-dependent activity against autologous primary B cells with reduced inflammatory cytokine production supporting KYV-101 as a novel potential therapy for the depletion of pathogenic B cells in SLE patients.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Chimeric antigen receptor; Cytokines; Systemic Lupus Erythematosus

Immune modulatory effects of Idelalisib in stromal cells of chronic lymphocytic leukemia - Handl, Sarah Annika; Von Heydebrand, Franziska; Völkl, Simon; Oostendorp, Robert A. J.; Wilke, Jochen; Kremer, Anita; Mackensen, Andreas; Lutzny-Geier, Gloria (Leukemia & Lymphoma, 2021)
Molecular targets of tyrosine kinase inhibitors are not restricted to the B-cell compartment but also regulate functions in the tumor microenvironment. Increasing evidence suggests that B-cell receptor-associated kinases like protein kinase C (PKC)-beta is essential for the formation of a microenvironment supporting leukemic growth. Here we describe the effect of Idelalisib on the PKC beta/NF-kappa B and Notch pathway in stromal cells upon contact to primary chronic lymphocytic leukemia cells (CLL). There is no Idelalisib-dependent regulation of the Notch expression in stromal cells, whereas Idelalisib induces PKC beta expression and activates the canonical NF-kappa B pathway. Idelalisib deregulates important immune-modulatory proteins in activated stromal cells, which might provoke the patient's side effects. Additionally, we established a 3D-stroma/leukemia model, that can give us a more defined look into the communication between tumor and stromal cells than standard cell cultures. This opens up the possibility to improve therapies, especially in the context of minimal-residual disease.
CRIS-Team WoS Importer:2021-05-28

Influence of DM-sensitivity on immunogenicity of MHC class II restricted antigens - Bernhardt, Anna Luise; Zeun, Julia; Marecek, Miriam; Reimann, Hannah; Kretschmann, Sascha; Bausenwein, Judith; van der Meijden, Edith; Karg, Margarete; Haug, Tabea; Meintker, Lisa; Lutzny-Geier, Gloria; Mackensen, Andreas; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Graft-versus-host-disease (GvHD) is a major problem in allogeneic stem cell transplantation. We previously described two types of endogenous human leukocyte antigen (HLA)-II restricted antigens depending on their behavior towards HLA-DM. While DM-resistant antigens are presented in the presence of HLA-DM, DM-sensitive antigens rely on the expression of HLA-DO-the natural inhibitor of HLA-DM. Since expression of HLA-DO is not upregulated by inflammatory cytokines, DM-sensitive antigens cannot be presented on non-hematopoietic tissues even under inflammatory conditions. Therefore, usage of CD4+ T cells directed against DM-sensitive antigens might allow induction of graft-versus-leukemia effect without GvHD. As DM-sensitivity is likely linked to low affinity peptides, it remains elusive whether DM-sensitive antigens are inferior in their immunogenicity. Methods We created an in vivo system using a DM-sensitive and a DM-resistant variant of the same antigen. First, we generated murine cell lines overexpressing either H2-M or H2-O (murine HLA-DM and HLA-DO) to assign the two model antigens ovalbumin (OVA) and DBY to their category. Further, we introduced mutations within the two T-cell epitopes and tested the effect on DM-sensitivity or DM-resistance. Furthermore, we vaccinated C57BL/6 mice with either variant of the epitope and measured expansion and reactivity of OVA-specific and DBY-specific CD4+ T cells. Results By testing T-cell recognition of OVA and DBY on a murine B-cell line overexpressing H2-M and H2-O, respectively, we showed that OVA leads to a stronger T-cell activation in the presence of H2-O demonstrating its DM-sensitivity. In contrast, the DBY epitope does not rely on H2-O for T-cell activation indicating DM-resistance. By introducing mutations within the T-cell epitopes we could generate one further DM-sensitive variant of OVA and two DM-resistant counterparts. Likewise, we designed DM-resistant and DM-sensitive variants of DBY. On vaccination of C57BL/6 mice with either epitope variant we measured comparable expansion and reactivity of OVA-specific and DBY-specific T-cells both in vivo and ex vivo. By generating T-cell lines and clones of healthy human donors we showed that DM-sensitive antigens are targeted by the natural T-cell repertoire. Conclusion We successfully generated DM-sensitive and DM-resistant variants for two model antigens. Thereby, we demonstrated that DM-sensitive antigens are not inferior to their DM-resistant counterpart and are therefore interesting tools for immunotherapy after allogeneic stem cell transplantation.
CRIS-Team Scopus Importer:2021-07-30
Keywords: adoptive; antigen presentation; antigens; CD4-positive T-lymphocytes; immunotherapy

Novel co-culture model of T cells and midbrain organoids for investigating neurodegeneration in Parkinson’s disease - Gerasimova, Elizaveta; Beenen, Amke; Kachkin, Daniil; Regensburger, Martin; Zundler, Sebastian; Blumenthal, David B.; Lutzny-Geier, Gloria; Winner, Beate; Prots, Iryna (npj Parkinson’s Disease, 2025)

Protein kinase C-β-dependent changes in the glucose metabolism of bone marrow stromal cells of chronic lymphocytic leukemia - Von Heydebrand, Franziska; Fuchs, Maximilian; Kunz, Meik; Kremer, Anita; Oostendorp, Robert A. J.; Wilke, Jochen; Leitges, Michael; Egle, Alexander; Mackensen, Andreas; Lutzny-Geier, Gloria; Völkl, Simon (Stem Cells, 2021)
Survival of chronic lymphocytic leukemia (CLL) cells critically depends on the support of an adapted and therefore appropriate tumor microenvironment. Increasing evidence suggests that B-cell receptor-associated kinases such as protein kinase C-β (PKCβ) or Lyn kinase are essential for the formation of a microenvironment supporting leukemic growth. Here, we describe the impact of PKCβ on the glucose metabolism in bone marrow stromal cells (BMSC) upon CLL contact. BMSC get activated by CLL contact expressing stromal PKCβ that diminishes mitochondrial stress and apoptosis in CLL cells by stimulating glucose uptake. In BMSC, the upregulation of PKCβ results in increased mitochondrial depolarization and leads to a metabolic switch toward oxidative phosphorylation. In addition, PKCβ-deficient BMSC regulates the expression of Hnf1 promoting stromal insulin signaling after CLL contact. Our data suggest that targeting PKCβ and the glucose metabolism of the leukemic niche could be a potential therapeutic strategy to overcome stroma-mediated drug resistance.
CRIS-Team Scopus Importer:2021-03-05
Keywords: BMSC; CLL; glucose metabolism; PKCβ

Severity of COVID-19 disease is related to hyperactivation and altered migratory capacity of T cells - Spörl, Silvia; Kremer, Anna-Lena; Aigner, Michael; Eisenhauer, Nina; Koch, P.; Meretuk, L.; Loeffler, P.; Lutzny-Geier, Gloria; Vetter, Marcel; Bruns, Heiko; Mackensen, Andreas; Kremer, Andreas; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Successful Generation of CD19 Chimeric Antigen Receptor T Cells from Patients with Advanced Systemic Lupus Erythematosus - Kretschmann, S.; Völkl, Simon; Reimann, Hannah; Krönke, Gerhard; Schett, Georg; Achenbach, Susanne; Lutzny-Geier, Gloria; Müller, Fabian; Mougiakakos, Dimitrios; Dingfelder, Janin; Flamann, Cindy; Hanssens, L.; et al. (Transplantation and Cellular Therapy, 2022)
Although it has been shown that the production of functional chimeric antigen receptor T cells is feasible in patients with B-cell malignancies, it is currently unclear whether sufficient amounts of functional autologous CAR T cells can be generated from patients with autoimmune diseases. Intrinsic T-cell abnormalities and T-cell–targeted immune suppression in patients with autoimmunity may hamper the retrieval of sufficient T cells and their transduction and expansion into CAR T cells. Patients with active systemic lupus erythematosus (SLE) underwent leukapheresis after tapering glucocorticoids and stopping T-cell–suppressive drugs. This material was used as source for manufacturing anti-CD19 CAR T-cell products (CAR) in clinical scale. Cells were transduced with a lentiviral anti-CD19 CAR vector and expanded under good manufacturing practice (GMP) conditions using a closed, semi-automatic system. Functionality of these CAR T cells derived from autoimmune patient cells was tested in vitro. Six SLE patients were analyzed. Leukapheresis could be successfully performed in all patients yielding sufficient T-cell numbers for clinical scale CAR T-cell production. In addition, CAR T cells showed high expansion rates and viability, leading to CAR T cells in sufficient doses and quality for clinical use. CAR T cells from all patients showed specific cytotoxicity against CD19+ cell lines in vitro. GMP grade generation of CD19 CAR T-cell products suitable for clinical use is feasible in patients with autoimmune disease.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Chimeric antigen receptor; Systemic lupus erythematosus; T cells

Successful treatment of COVID-19 infection with convalescent plasma in B-cell-depleted patients may promote cellular immunity - Kremer, Andreas E.; Kremer, Anita; Willam, Carsten; Völkl, Simon; Verhagen, Johan; Achenbach, Susanne; van der Meijden, Edith; Lang, Vanessa; Aigner, Michael; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; et al. (European Journal of Immunology, 2021)
Treatment with convalescent plasma has been shown to be safe in coronavirus disease in 2019 (COVID-19) infection, although efficacy reported in immunocompetent patients varies. Nevertheless, neutralizing antibodies are a key requisite in the fight against viral infections. Patients depleted of antibody-producing B cells, such as those treated with rituximab (anti-CD20) for hematological malignancies, lack a fundamental part of their adaptive immunity. Treatment with convalescent plasma appears to be of general benefit in this particularly vulnerable cohort. We analyzed clinical course and inflammation markers of three B-cell-depleted patients suffering from COVID-19 who were treated with convalescent plasma. In addition, we measured serum antibody levels as well as peripheral blood CD38/HLA-DR-positive T-cells ex vivo and CD137-positive T-cells after in vitro stimulation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-derived peptides in these patients. We observed that therapy with convalescent plasma was effective in all three patients and analysis of CD137-positive T-cells after stimulation with SARS-CoV-2 peptides showed an increase in peptide-specific T-cells after application of convalescent plasma. In conclusion, we here demonstrate efficacy of convalescent plasma therapy in three B-cell-depleted patients and present data that suggest that while application of convalescent plasma elevates systemic antibody levels only transiently, it may also boost specific T-cell responses.
CRIS-Team Scopus Importer:2021-09-17
Keywords: B-cell deficiency; convalescent plasma; COVID-19; SARS-CoV-2; T-cell immunity

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Targeted Inhibition of Protein Biosynthesis sensitizes Cancer Cells to IRE1a-mediated Apoptosis as a Consequence of the unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, S.; Wendland, Kerstin; George, Rebekka; Petkovic, S.; Mellenthin, Lisa; Emmerich, C.; Lutzny-Geier, Gloria; Mackensen, Andreas; Metzler, Markus; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Targeted inhibition of protein synthesis renders cancer cells vulnerable to apoptosis by unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (Cell Death & Disease, 2023)
Cellular stress responses including the unfolded protein response (UPR) decide over the fate of an individual cell to ensure survival of the entire organism. During physiologic UPR counter-regulation, protective proteins are upregulated to prevent cell death. A similar strategy induces resistance to UPR in cancer. Therefore, we hypothesized that blocking protein synthesis following induction of UPR substantially enhances drug-induced apoptosis of malignant cells. In line, upregulation of the chaperone BiP was prevented by simultaneous arrest of protein synthesis in B cell malignancies. Cytotoxicity by immunotoxins—approved inhibitors of protein synthesis—was synergistically enhanced in combination with UPR-inducers in seven distinct hematologic and three solid tumor entities in vitro. Synergistic cell death depended on mitochondrial outer membrane permeabilization via BAK/BAX, which correlated with synergistic, IRE1α-dependent reduction of BID, accompanied by an additive fall of MCL-1. The strong synergy was reproduced in vivo against xenograft mouse models of mantle cell lymphoma, Burkitt’s lymphoma, and patient-derived acute lymphoblastic leukemia. In contrast, synergy was absent in blood cells of healthy donors suggesting a tumor-specific vulnerability. Together, these data support clinical evaluation of blocking stress response counter-regulation using inhibitors of protein synthesis as a novel therapeutic strategy.
CRIS-Team Scopus Importer:2023-09-08

Upregulation of CCR4 in activated CD8(+) T cells indicates enhanced lung homing in patients with severe acute SARS-CoV-2 infection - Spoerl, Silvia; Kremer, Anita; Aigner, Michael; Eisenhauer, Nina; Koch, Pauline; Meretuk, Lina; Loeffler, Patrick; Tenbusch, Matthias; Maier, Clara; Überla, Klaus; Heinzerling, Lucie; Frey, Benjamin; et al. (European Journal of Immunology, 2021)
COVID-19 is a life-threatening disease leading to bilateral pneumonia and respiratory failure. The underlying reasons why a smaller percentage of patients present with severe pulmonary symptoms whereas the majority is only mildly affected are to date not well understood.
CRIS-Team WoS Importer:2021-05-07